Pengaruh Media Sosial Facebook dan Brand Performance Pipa Merek Rucika terhadap Minat Beli Konsumen di PT. Laksamanakarya Adiyasa - Kusdiana, Taufan; Saputra, Munir (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2023)
Significant development of technology has driven changes from conventional communication to modern and digital one, and nowadays sales conducted through internet have flourished. Even, not only well-known brands are sold through internet media. Therefore, companies can use selling strategies through internet media, supported by brand performance from products to boost consumer buying interest. This thesis used quantitive and associative research methods aimed to discover how big the influence of social media Facebook and brand performance of pipe brand Rucika is against consumer buying interest. Respondents in this research were the customers of PT Laksamanakarya Adiyasa. Samples were determined using questionnaire technique to respondents, interview, and documentation. To prove and analyze the foregoing, literary study, field study, reliability test, validity test, and hypothesis test were conducted. The result indicates that: 1) Social media Facebook has no influence over consumer buying interest. It is concluded from the result of T test to social media Facebook as variable X1 namely 0.756 which is ≥ 0.05. 2) Brand performance influences consumer buying interest. It is concluded from the result of T test of variable X2 to Y namely 0.014 which is ≤ 0.05. 3) Social media Facebook and brand performance influence consumer buying interest. It is concluded from the result of F test by calculating variables X1 and X2 against Y namely 3.163 which is ≥ F table 3.114, then it is concluded that all hypotheses are accepted.